THE IMPACT OF TECHNOLOGY ON ENGLISH LANGUAGE ACQUISITION AMONG UNIVERSITY STUDENTS (Educator Insights: Journal of Teaching Theory and Practice, 2026)
The rapid development of technology has significantly transformed the process of English language acquisition among university students. Digital tools such as mobile applications, online learning platforms, and multimedia resources provide learners with interactive and flexible learning environments. These technologies enhance students’ listening, speaking, reading, and writing skills by offering real-time feedback, authentic materials, and opportunities for communication with native speakers. Moreover, technology promotes autonomous learning and increases student motivation. However, challenges such as overreliance on technology, lack of digital literacy, and distractions may negatively affect learning outcomes. This study explores both the positive and negative impacts of technology on English language acquisition and highlights its role in modern higher education.